Decision making style, generation, and social stratification: An explorative study of Indonesia consumer - Triwijayati, Anna (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This paper seeks to examine the differentiating effect of Consumer Decision Makin Style (CDMS) from social class and generation of Indonesia consumer. CDMS is measured using the Consumer Style Inventory (CSI) indicators. Methodology/approach – A survey that included information on descriptive research. One thousand Indonesian consumers from various social classes and generations were involved as respondents. Data were analysed using ANOVA. Findings – It was found that each generation has its own CDMS. Generation Z tends to have Novelty-Brand, less-Impulsive, Habitual, and less Financial-Time-Energy Consciousness. Generation Y tends to have Perfection-Quality and Recreational styles. Generation X tends to have a less Variability style. Meanwhile, the Baby Boomer generation is less in CDMS characteristics. In all generations, there is no difference in CDMS in Confused by Over choice and Variability styles. Based on social class, there are differences in CDMS for Perfection-Quality, Confused by Over choice, Recreational, Impulsive, Variability, Habitual, and Financial-Time-Energy Consciousness, but there are no differences in Novelty-Brand Consciousness. Novelty/value – CDMS is measured using the Consumer Style Inventory (CSI) indicator. Unfortunately, CSI is developed limited to developed countries. However, with the research base in the US, CSI data in developing countries is lacking. In Indonesia, CDMS may differ according to market segments. This study has impacts on the CDMS mapping of Indonesian consumer segments where marketers can direct appropriate marketing strategies to each segment